Comparison of the effectiveness between 2% and 4% nicotinamide gel in reducing melanin index - Lisa Murtisari Lisa Murtisari (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2005)
Background: Nicotinamide is a safe agent inhibiting melanosome transfer in vitro therefore it can reduce skin pigmentation. Two percent nicotinamide cream combined with sunscreen as a lightening agent in-creases skin lightness in vivo. Measurement of skin colour changes can be performed by mexameter to measure melanin index (MI).Objective: This study was aimed to compare the effectiveness of 2% and 4% nicotinamide gel as a lightening agent in reducing MI.Materials and Methods: This study was a double blind, randomized controlled trial involving 54 subjects. Two percent or 4% nicotinamide gel was applied on extensor right or left lower arm in each subject. MI was measured at week 0 and the end of week 1, 3, 5 and 7. MI in the evaluation weeks was compared to MI at week 0 in the 2% and 4% nicotinamide gel groups and was analyzed using paired-t test. MI decrease in the evaluation weeks between 2% and 4% nicotinamide gel groups were analyzed using independent t test. All statistical tests used a 5% and CI 95%.Result: Statistical analysis in the 2% nicotinamide gel group showed significant decrease in MI until week 7. However, in the 4% nicotinamide gel group there were significant MI decrease in the week 5 and 7. Statistical analysis showed significant decreased MI between 2% and 4% nicotinamide gel groups at week 1, 3, 5, 7.Conclusion: It was concluded that 4% nicotinamide gel had higher effectiveness compared to 2% in reducing MI as lightening agent.Key words: nicotinamide gel, melanin index, skin colour, lightening agent